The Risk of Long-Term Financing of Public Investments (European Journal of Marketing and Economics, 2019)
The risk of financing of public investments is a phenomenon that accompanies development processes in a permanent manner. Investments in the public sector are generally characterized by relatively long implementation cycles and involve significant capital expenditure and the necessity of often parallel running a large number of investment projects. In the processes of this type of investment a specific risk category of financing of this type of investment is quite often taken into account, given that such projects are financed mainly from budgetary resources: the state budget and self-government budgets. Economic practice indicates an importance of the proper selection of the method of the financing of new investments and taking into account new funds from various sources. This situation is often the result of a shortage of budgetary resources from which public investments could be financed. There may be difficulties in financing investments resulting from the emergence of a risk of budgetary deficit and the public debt. This risk may have a negative impact on investment decisions and may adversely affect the future course of ongoing investment projects. The purpose of the paper is to undertake studies on the conditions of financing investments from the point of view of the possibility of budget deficit and public debt and the impact of changes in the financial situation on the overall level of risk of public investment. The text is an invitation to undertake a broader discussion on financing public investments in conditions of limited public financial resources.
Keywords: investment risk, budgetary economy, public finance, decision making.